Downdrag Loads Developed by a Floating Ice Cover: Field Experiments - Frederking, R. (Canadian Geotechnical Journal, 1974)
The first phase of an investigation of the vertical forces developed on a structure by a floating ice cover frozen to it is described. It is the objective of this work to develop the theoretical, experimental, and field aspects of vertically acting loads required for the more efficient design of structures subject to such loads. A load frame was constructed that would apply constant upward acting loads to wooden piles frozen into an ice cover composed mainly of snow ice. Load, ice temperatures, and movement of the pile in relation to the ice were measured.The time-dependent movement of the pile in relation to the ice exhibited creep characteristics, and these results were related to shear creep for grouted rod anchors in permafrost. Results of a previous study for WF steel H-beams in ice were also considered. The steady-state creep displacement rate for wooden piles in ice, rod anchors in permafrost, and WF steel H-beams in ice exhibited a comparable dependence on the constant applied shear stress. The steady-state creep displacement rate of a 100-mm wooden pile in snow ice at −3 °C and under a constant applied shear stress of 180 kN/m 2 was about 1 mm/day.